Carbonaceous aerosols in urban Chongqing, China: Seasonal variation, source apportionment, and long-range transport. (December 2021) - Feng, Ting; Wang, Fengwen; Yang, Fumo; Li, Zhenliang; Lu, Peili; Guo, Zhigang
Abstract: Seventy-seven PM2.5 samples were collected at an urban site (Chongqing University Campus A) in October 2015 (autumn), December 2015 (winter), March 2016 (spring), and August 2016 (summer). These samples were analysed for organic carbon (OC), elemental carbon (EC), and their associated char, soot, 16 PAHs, and 28 n-alkanes to trace sources, and atmospheric transport pathways. The annual average of OC, EC, char, soot, ΣPAHs, and Σn-alkanes were 20.75 μg/m 3, 6.18 μg/m 3, 5.43 μg/m 3, 0.75 μg/m 3, 38.29 ng/m 3, and 328.69 ng/m 3, respectively. OC, ΣPAHs, and Σn-alkane concentrations were highest in winter and lowest in summer. EC, char, and soot concentrations were highest in autumn and lowest in winter. Source apportionment via positive matrix factorization (PMF) indicated that coal/biomass combustion-natural gas emissions (23.8%) and motor vehicle exhaust (20.2%) were the two major sources, followed by diesel and petroleum residue (21.1%), natural biogenic sources (17.7%), and evaporative/petrogenic sources (17.2%). The highest source contributor in autumn and winter was evaporative/petrogenic sources (30.6%) and natural biogenic sources (34.5%), respectively, whereas diesel engine emission contributed the most in spring and summer (32.1% and 38.0%, respectively). Potential source contribution function (PSCF) analysis identified southeastern Sichuan and northwestern Chongqing as the major potential sources of these pollutants. These datasets provide critical information for policymakers to establish abatement strategies for the reduction of carbonaceous pollutant emissions and improve air quality in Chongqing and other similar urban centres across China. Highlights: An obvious seasonal variation of carbonaceous aerosols was observed. Qualitative sources apportioned using OC/EC and char/soot complemented well each other. Five sources of OC, EC, PAHs and n-alkanes were apportioned using PMF. PSCF identified southeast Sichuan and northwestern Chongqing as potential major source areas.